CLEAR technology. Clinical and functional results of more than 1000 corrections of myopia and myopic astigmatism - T.S. Kuznetsova; V.D. Antonuk; S.Yu. Shchukin; I.V. Drozdov; O.I. Kuranova (Офтальмохирургия)
Purpose. To evaluate the clinical and functional results of correction of myopia and myopic astigmatism using CLEAR technology. Material and methods. In Eye Microsurgery Gazprom Clinic, 1252 CLEAR surgeries (626 patients) were performed on the platform of the LDV Z8 femtosecond laser (Ziemer) in the period from October 2021 to May 2023. Gender distribution: 219 males (35%) and 407 females (65%). The follow-up period was from 4 months to 12 months. The age of the patients ranged from 16 to 49 years (32.04±6.74 years). Sph from –0.25 to –9.0 D (–3.76±1.48 D), cyl from –0.0 to –2.25 D (–0.53±0.34 D), uncorrected visual acuity was 0.07±0.06, and best corrected visual acuity ranged from 0.8 to 1.0 (0.99±0.01). Central corneal thickness (CCT) (according to ultrasound keratopachimetry) ranged from 487 to 634 microns (552.9±28.7 microns). Horizontal diameter of the cornea was from 10.9 to 13.4 mm (12.1±0.37 mm). Average curvature of the cornea in the center (Average K) ranged from 39.5 to 47.25 D (43.39±1.32 D). Results. Uncorrected visual acuity at 1st day after surgery (1252 eyes) was 0.93±0.2, sph –0.11±0.5 D, cyl –0.4±0.5 D; uncorrected visual acuity after 4–6 months (323 eyes) 1.05±0.24, sph –0.16±0.5 D, cyl –0.4±0.5D; uncorrected visual acuity after 9–12 months (44 eyes) 1.04±0.2, sph –0.11± 0.4D, cyl –0.5±0.6D. Safety index 1.0, efficiency index 1.05. Percentage of intraoperative and early postoperative period complications was less than 1%. Conclusion. Correction of myopia and myopic astigmatism using CLEAR technology is a predictable, safe, effective technology.